Labour Migration and Cross-Cultural Encounters: Welsh Copper Workers in Chile in the Nineteenth Century - Jones, Bill (Revista de Historia Social y de las Mentalidades, 2024)
The transference of copper smelting technology from the swansea area that accompanied the development of the world copper industry in the nineteenth century has yet to be studied in detail. This article begins to redress this omission by focusing largely on a micro history of welsh copper smelters who migrated to guayacán, near Coquimbo Chile, in the middle decades of the nineteenth century. It examines the development of a welsh labour presence in Guayacán and the dynamics of the migration, including motives, networks and recruitment processes. It also explores how the possession of industrial skills shaped cultural and religious encounters between the welsh and chileans.
Keywords: Migration; Chile; Wales; Copper Smelting; Cultural and Religious Encounters